The Determination of the Flow Rate by Measuring the Absorption of Beta Rays - Tabakflussmengenmessung mittels Beta-Strahlung - Marek J.; Hayn G. (Contributions to Tobacco and Nicotine Research, 1968)
The experiments made reveal that the principle of determining the rate of flow by measuring the absorption of beta rays is suitable for industrial application in the field of tobacco processing. The advantages of the procedure are the free installation and the small dimensions of the device. The price of the apparatus is surprisingly low, its application is, therefore, expedient mainly as transducer for controlling the flow rate of additives. The precision of the procedure satisfies most purposes being constant over long periods of time and not depending on factors such as, for example, the formation of a layer sticking to the surface of the belt weigher. There is, furthermore, the possibility of measuring the rate of tobacco flow in pneumatic conveyors.